Fifteenth General Review of Quotas : Additional Considerations and Data Update. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2021)
This paper provides background for a further round of discussions on the Fifteenth General Review of Quotas (hereafter 15th Review). The paper builds on work presented in previous staff papers and Directors' views expressed in three meetings of the Committee of the Whole in September 2017 and February 2018. No proposals are presented at this stage, pending further Board guidance on possible approaches to narrowing the current differences of views.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Current Account Adjustment; Short-Term Capital Movements